Effect of 12-hour fire on Flexural Behavior of Recyclable Aggregate Reinforced Concrete Beams - Abdul Hafeez Buller; Bashir Ahmed Memon; Mahboob Oad (Salehan Institute of Higher Education, 2019)
Fire being one of the hazards causes external and internal adverse effects on concrete. On the other hand, demolishing waste causes numerous environmental issues due to lack of proper disposal management. Therefore, this research work presents experimental evaluation of effect of 12-hur fire on flexural behavior of reinforced concrete beams made with partial replacement of natural coarse aggregates with coarse aggregates from demolished concrete. The model beams are prepared using both normal and rich mix. Natural coarse aggregates are replaced in 50% dosage. Also, the beams without recyclable aggregates are prepared to check the results of proposed beams. After 28-day curing all the beams are exposed to fire for 12-hour at 1000°C in purpose made oven, followed by testing in universal load testing machine under central point load. During the testing deflection, load, and cracks are monitored. Analysis of flexural behavior and cracking reveals that after 12-hour fire residual strength of the beams is 52%. This shows loss of the strength of reinforced concrete beams thus requires appropriate retrofitting decision before putting again the structure in service after fire. Observation of cracks shows that most of the beams failed in shear with minor flexural cracks. In comparison to the results of control specimen the proposed beams show good fire resistance. The outcome of the research will prove landmark for future scholars and help the industry personals in understanding the behavior of the material in fire.